Glacier mass balance and its climatic and nonclimatic drivers in the Ladakh region during 2000-2021 from remote sensing data - Mandal, Arindan; Vishwakarma, Bramha Dutt; Angchuk, Thupstan; Azam, Mohd Farooq; Garg, Purushottam Kumar; Soheb, Mohd (Journal of glaciology, 2024)
This study investigates the geodetic mass balance of nearly all glaciers in the Ladakh region, which are crucial for local water security. Utilizing multiple digital elevation models from 2000 and 2021, we estimate glacier mass balances. Climatic drivers of glacier mass balances are explored using ERA5-Land reanalysis data, evaluated by in situ climate data. The study also examines the role of nonclimatic (morphological) variables on glacier mass balances. Results indicate Ladakh glaciers experienced negative mass balances during 2000-2021, with significant spatial variability. Western Ladakh glaciers lost slightly higher mass (−0.35 ± 0.07 to −0.37 ± 0.07 m w.e. a−1) than eastern Ladakh glaciers (−0.21 ± 0.07 to −0.33 ± 0.05 m w.e. a−1). While warming is the main driver of widespread mass loss in Ladakh, the spatial variability in mass loss is attributed to changes in regional precipitation and glacier morphological settings. Eastern Ladakh glaciers, being smaller and at higher elevations, experience lower mass loss, whereas western Ladakh glaciers, larger and at lower elevations, are more susceptible to the impact of temperature, resulting in higher mass loss. The study underscores the potentially greater vulnerability of western Ladakh glaciers to a warming climate compared to their eastern counterparts.